EFFECT OF GROWTH MEDIA AND GROWTH REGULATORS ON THE GROWTH OF CORN FODDER PLANTS (ZEA MAYS L.) - Wenda, Danur
Forage given to livestock serves to meet the nutritional needs of livestock. In densely populated areas, forage production has decreased every year due to limited land. One effort that can be done to increase the production of forage on limited land is by making corn fodder. Corn fodder production is optimal when sufficient water is available for growth. This study aimed to analyze the effect of different types of planting media and concentrations of growth regulators (PGR) with m1p1 (without media; without PGR), m1p2 (without media; IAA 10 M), m1p3 (without media; BAP 10 M), m1p4 (without media; IAA 10 M + BAP 10 M), m2p1(burnt rice husk; without ZPT), m2p2(rice roasted husk; IAA 10 M), m2p3(burned rice husk; BAP 10 M), m2p4(burned rice husk ; IAA 10 M + BAP 10 M), m3p1(cocopeat; without ZPT), m3p2(cocopeat; IAA 10 M), m3p3(cocopeat; BAP 10 M), m3p4(cocopeat; IAA 10 M + BAP 10 M), m4p1 (frosted paper; no ZPT), m4p2(frosted paper; IAA 10 M), m4p3 (frosted paper; BAP 10 M), and m4p4(frosted paper; IAA 10 M + BAP 10 M). on plant height, root wet weight, root dry weight, canopy wet weight, and canopy dry weight of corn fodder (Zea mays). The results showed that there was no interaction between the use of the type of planting media and growth regulators. Provision of cocopeat planting media resulted in the highest corn fodder plant height at 11 (Day After Planting) DAP (24.64 cm), wet weight of corn fodder crown (52.86 grams), dry weight of corn fodder crown (3.24 grams), wet weight of corn fodder roots ( 102.15 grams), and dry weight of corn fodder roots (2.08 grams). The application of growth regulators tended to give the best results at 11 DAP (20.75 cm) height of fodder maize plant, wet weight of maize fodder crown (47.94 gram), dry weight of maize fodder crown (3.16 gram), wet weight of fodder root corn (94.54 grams), and root dry weight of corn fodder (2.07 grams).